(untitled) (KIUT Publication, 2025)
Materials and Methods: A clinical observation was conducted on a 12-year-old male patient with a confirmed diagnosis of Hemophilia A. The patient presented with complaints of recurrent spontaneous bleeding, hemarthrosis (bleeding into joints, primarily knees and elbows), and soft tissue hematomas. Medical history collection included family history of Hemophilia A (affecting the mother, two younger brothers, and maternal grandfather).